PREHISPANIC MAYA BURNT LIME INDUSTRIES: PREVIOUS STUDIES AND FUTURE DIRECTIONS. Issue 2 (2019) - Seligson, Kenneth E.; Ortiz Ruiz, Soledad; Barba Pingarrón, Luis
Abstract: Burnt lime has played a significant role in daily Maya life since at least as far back as 1100b.c., and yet its ephemeral nature has limited archaeological studies of its production. The application of new surveying and remote sensing technologies in recent decades is now allowing for a more in-depth investigation of the burnt lime industries that existed in different subregions of the Maya area. This article provides an overview of the current understanding of pre-Hispanic Maya burnt lime production. It then presents an analysis of the factors influencing the development and identification of distinct subregional lime production industries, including: lime consumption requirements and inter-site spacing; natural environment; local social and economic trajectories; and the objectives and survey universes of archaeological investigations. In reporting the tremendous advances made over the past few decades, this paper encourages archaeologists to include a focus on identifying lime production features in their research agendas.